2011
DOI: 10.1103/physrevb.83.165205
|View full text |Cite
|
Sign up to set email alerts
|

Variable-range hopping conduction in epitaxial CrN(001)

Abstract: Epitaxial CrN(001) layers, grown by dc magnetron sputtering on MgO(001) substrates at growth temperatures T s = 550-850 °C, exhibit electronic transport that is dominated by variablerange-hopping (VRH) at temperatures <120 K. A transition from Efros-Shklovskii (ES) to Mott VRH at 30±10 K is well described by a universal scaling relation. The localization length decreases from 1.3 nm at T s = 550 °C to 0.9 nm for T s = 600-750 °C but increases again to 1.9 nm for T s = 800-850 °C, which is attributed to changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 69 publications
(122 reference statements)
7
46
0
Order By: Relevance
“…This behavior contrasts with the Seebeck coefficient values which matches that of n-type semiconducting. A likely explanation is that the nitrogen vacancies are acting as donors by greatly increase the charge carrier density, creating non-zero quasi-metallic density of states at the Fermi level for the sample [57,58]. In this case, a rise in the temperature will probably enhance electron-electron scattering resulting in a small decrease in the conductivity values.…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%
“…This behavior contrasts with the Seebeck coefficient values which matches that of n-type semiconducting. A likely explanation is that the nitrogen vacancies are acting as donors by greatly increase the charge carrier density, creating non-zero quasi-metallic density of states at the Fermi level for the sample [57,58]. In this case, a rise in the temperature will probably enhance electron-electron scattering resulting in a small decrease in the conductivity values.…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%
“…3,4 Considerable experimental and theoretical work have demonstrated that CrN undergoes a magnetic and structural phase transition from a paramagnetic NaCl structure at room temperature to a low-temperature antiferromagnetic orthorhombic P nma phase at N eel temperature of 273-286 K. [5][6][7] A variety of electrical transport properties in CrN have been observed, such as, a semiconducting behavior with dq/dT < 0, [8][9][10][11] a metallic behavior with dq/dT > 0, [12][13][14] and continuous and discontinuous q(T) curves at 260-280 K. [8][9][10][11][12][13]15 These differences in electrical transport properties have been attributed to the sensitivity of the transport properties to N stoichiometry. 12,15 In addition, the discontinuity in q(T) curves has usually been observed in CrN powders or polycrystalline CrN films, rather than in epitaxial films, suggesting that the epitaxial constraints could affect the transition.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Here, we use a universal scaling relation considering both Mott VRH and ES hopping, which has previously been reported for epitaxial CrN(001) films by Zhang et al 11 The expression first proposed by Aharony et al 27 is…”
mentioning
confidence: 99%
“…3,4 Electronic transport studies report controversial results for CrN, including (i) values for the resistivity ρ at room temperature range over more than two orders of magnitudes, from 1.7×10 -3 to 3.5×10 -1 Ωcm, 3,[5][6][7][8][9][10] even when only considering the most reliable data for single crystal CrN layers; (ii) the temperature dependence of ρ shows metallic behavior with dρ/dT > 0 in some studies, 6,7,11 but an increase in ρ with decreasing temperature in other reports, 3,5,9,12 which has been attributed to the presence of a band gap 5 or carrier localization due to crystalline defects 13 or N-vacancies; 14 (iii) some studies report a discontinuity in ρ(T) at 260-280 K, 3,6,7,14 which is associated with a magnetic and structural phase transition from a paramagnetic NaCl structure at room temperature to a low-temperature antiferromagnetic orthorhombic P nma phase 11,15 with a 0.56-0.59% higher density, 11 and a 25% lower bulk modulus, 16 while other reports show no evidence for a phase transition in the ρ(T)-curves. 5,7,9 Electronic structure calculations suggest that magnetic stress relief couples magnetic ordering with the structural phase transition, 17 and that CrN exhibits a band gap if the Hubbard Coulomb interaction term is sufficiently large.…”
mentioning
confidence: 99%